2020
DOI: 10.1111/nuf.12521
|View full text |Cite
|
Sign up to set email alerts
|

E‐learning: Depression, anxiety, and stress symptomatology among Lebanese university students during COVID‐19 quarantine

Abstract: Background E‐learning has been adopted internationally as the alternative teaching or learning strategy during the coronavirus disease 2019 (COVID‐19) quarantine to fill the academic gap that has been created by the existing reality of the pandemic due to nationwide closures. Aim This study aims at evaluating the prevalence of depression, anxiety, and stress symptomatology among Lebanese University Students during the COVID‐19 Quarantine. Methodology A quantitative cross sectional research design, where 520 un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
250
5
12

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(367 citation statements)
references
References 19 publications
18
250
5
12
Order By: Relevance
“…A total of 476 university students living in Bangladesh reported that around 15% of them had moderately severe depression, whereas 18.1% were suffering from severe anxiety (Islam et al, 2020). Furthermore, a study of 520 Lebanese university students showed that 15.5% of the students had at least moderate depressive symptoms, and 30.5% reported anxiety symptoms (Fawaz & Samaha, 2021). The depression and anxiety symptoms were reported comparing with stress symptoms among the HEI students in this study.…”
Section: Discussionmentioning
confidence: 49%
“…A total of 476 university students living in Bangladesh reported that around 15% of them had moderately severe depression, whereas 18.1% were suffering from severe anxiety (Islam et al, 2020). Furthermore, a study of 520 Lebanese university students showed that 15.5% of the students had at least moderate depressive symptoms, and 30.5% reported anxiety symptoms (Fawaz & Samaha, 2021). The depression and anxiety symptoms were reported comparing with stress symptoms among the HEI students in this study.…”
Section: Discussionmentioning
confidence: 49%
“…The reasons for dissatisfaction with the online learning system are bad and connection disruptions which can occur when class sessions take place which require students to leave and enter sessions, data loss, and schedule power outages that even prevent students from taking classes to online exams. 7 The semester level also has a significant difference in the negative impact of online learning. Students who are in the second year of university have higher negative effects, levels of anxiety and depression than first-year students.…”
Section: Discuss Student Perspective On Distance Learningmentioning
confidence: 99%
“…This can occur as a result of drastic changes in the learning system and environment, as well as thoughts about their future career prospects. 13,7 Intervention. Several interventions can be carried out to ease the psychological burden on students through distance learning during the COVID-19 pandemic.…”
Section: Impact Of Distance Learning On Studentsmentioning
confidence: 99%
“…Al respecto, en el Líbano se encontraron prevalencias importantes de estrés (12,7% de leve a moderado) en estudiantes universitarios como resultado de la pandemia de COVID-19, esencialmente por los cambios en la impartición de la enseñanza (3), en Jordania los niveles de estrés en los estudiantes fueron mayores (32%) en periodos de exámenes remotos (4). Los niveles de estrés se acentúan en los estudiantes que pertenecen a las ciencias de la salud, por tener un vínculo cercano con la atención de pacientes y por la naturaleza de las materias; así lo demuestra un estudio desarrollado con estudiantes de enfermería en España, que obtuvo niveles altos de estrés durante el confinamiento por la pandemia de COVID-19 en relación a los niveles de estrés presentados antes del encierro (5).…”
Section: Introductionunclassified